Influence of storage time on vitrified human cleavage-stage embryos froze in open system. (1st February 2017) - Li, Wei; Zhao, Wanqiu; Xue, Xia; Zhang, Silin; Zhang, Xin; Shi, Juanzi
Abstract: Background : During in vitro fertilization, rapid growth of vitrification and liquid nitrogen storage of embryos have been well characterized. However, the effect of storage time on vitrified cleavage-stage embryos in an open system is poorly understood. Aims : To investigate the influence of storage time on the survival and pregnancy outcomes of vitrified human cleavage-stage embryos froze and stored in an open system. Methods : A retrospective study of 786 vitrified-warmed cycles of 735 patients was performed from January 2013 to October 2013. The cycles were divided into five groups according to storage time: 1–3 months, 4–6 months, 7–12 months, 13–24 and 25–60 months. The clinical outcomes of cycles with different storage time were analyzed. Results : There were no significant differences of the survival rate, clinical pregnancy outcomes, birth rate, gestational weeks and singleton birthweights at various storage times. Conclusion : For vitrified embryos froze and stored in an open system, the storage time would not influence the survival rate and pregnancy outcomes by storage time up to 5 years.